(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background and objectives: Dementia is characterized by loss of or decline in memory and other cognitive abilities and reduces the lifespan of affected people. The number of people with Alzheimer’s Disease and other dementias is increasing every year because of the steady growth in the older population and stable increment in life expectancy and it is expected to increase two-fold by 2030 and three-fold by 2050.In addition to Alzheimer’s disease there are so many reversible and irreversible causes of dementia. This study was aimed to explore the different etiological factors related to dementia patients. Risk factors for dementia, co-morbid conditions were also included. Methods: This cross sectional study was carried out from 2009 to 2014 at dementia clinic (OPD), department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU). A total number of 166 dementia patients, as diagnosed by Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and confirmed by Mini Mental State Examination(MMSE) score were recruited in this study. Diagnosis of specific type of dementia was made on the basis of established criteria. Results: Alzheimer’s disease(32.5%) and Vascular dementia(31.9%) were the most common etiological factor followed by Mixed dementia(19.9%), PD with dementia(8.4%) and others(7.2%) like hypothyroidism, head injury, epilepsy etc. Increasing age, hypertension, diabetes mellitus, dyslipidemia, IHD, smoking are potential risk factors for dementia. Conclusion: This study concludes Alzheimer’s disease and Vascular dementia are almost equally occurring dementia. There are also some potential risk factors for development of dementia whose modification can bring a great change in dementia treatment and functional outcome of this group of elderly people of Bangladesh. Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 77-83